2003
DOI: 10.1046/j.1365-2036.2003.01745.x
|View full text |Cite
|
Sign up to set email alerts
|

Once‐daily pantoprazole 40 mg and esomeprazole 40 mg have equivalent overall efficacy in relieving GERD‐related symptoms

Abstract: SUMMARYAim: To compare the efficacy of pantoprazole and esomeprazole for the treatment of gastro-oesophageal reflux disease-(GERD-) related symptoms. Methods: In this multicentre, randomized, double-blind study 217 patients [intention-to-treat (ITT) Patients recorded GERD-related symptoms (daytime and night-time) using diaries (daily), and/or by telephone interviews (every third day) and completed the Gastrointestinal Symptom Rating Scale (GSRS) questionnaire. The area under the time curve (AUC) for the sum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 34 publications
1
44
0
1
Order By: Relevance
“…1,4 The recently introduced (S)-isomer of OME, esomeprazole (ESO), may provide more effective gastric acid control than standard doses of the other PPIs, 5 but may not afford a better clinical response than other PPIs. 6,7 The effect of PPIs on the results of the 13 C UBT appears to be due to a pH-dependent mechanism. [8][9][10] Previously published reports have described false negative rates of 17-38% for 20 mg/day OME after 14 days.…”
Section: Introductionmentioning
confidence: 99%
“…1,4 The recently introduced (S)-isomer of OME, esomeprazole (ESO), may provide more effective gastric acid control than standard doses of the other PPIs, 5 but may not afford a better clinical response than other PPIs. 6,7 The effect of PPIs on the results of the 13 C UBT appears to be due to a pH-dependent mechanism. [8][9][10] Previously published reports have described false negative rates of 17-38% for 20 mg/day OME after 14 days.…”
Section: Introductionmentioning
confidence: 99%
“…Both drugs were safe well-tolerated. 18 Gillessen et al 19 and Scholten et al 20 have reported similar effectiveness for esomeprazole 40 mg and pantoprazole 40 mg, or even greater effectiveness for latter drug in terms of speed of symptom resolution. Crossover studies in healthy subjects and patients with symptoms of GERD have shown that esomeprazole is more effective than all other PPI for providing greater time with pH >4.…”
Section: Discussionmentioning
confidence: 95%
“…However, to date there is no undisputed evidence of an appreciable difference in effectiveness between different PPIs at equivalent doses. In fact, clinical studies have not demonstrated any consistent difference between PPIs at similar doses with regard to clinical or endoscopic outcomes [2,15,16,17, 28]. …”
Section: Discussionmentioning
confidence: 99%
“…Esomeprazole and pantoprazole are both very effective and prove therapeutic equivalence in case of GERD [15,16,17], and are indicated for the treatment of enGERD, achieving adequate short-term symptom relief rates, particularly heartburn, and effective subsequent long-term symptomatic remission rates [18,19,20,21]. However, the prime concerns for many GERD patients, particularly for those with enGERD, are fast relief of pain and subsequently sustained symptom control, and therefore not only relief rates at a fixed date (e.g.…”
Section: Introductionmentioning
confidence: 99%